Imaging Assessment of Thoracic Cage Injuries - Iacobellis, Francesca; Iadevito, Isabella; Ierardi, Anna Maria; Carrafiello, Gianpaolo; Perillo, Federica; Nicola, Refky; Scaglione, Mariano (Seminars in Musculoskeletal Radiology, 2017)
Thoracic injuries are the third most common traumatic injury. Approximately two thirds of thoracic injuries are due to motor vehicle collisions. They are associated with up to a 20% mortality rate. This is primarily due to the presence of several complex anatomical structures within the thoracic cage such as the heart, great vessels, esophagus, airways, lungs, mediastinum, bones, muscles, diaphragm, and pleura. A chest radiograph is the initial imaging modality in the evaluation of the chest. However, multidetector computer tomography (MDCT) with intravenous contrast is the imaging modality of choice in the assessment of acute thoracic injuries.Endovascular repair is less invasive and has a better outcome than traditional surgical repair. This review article discusses the indications, benefits, and findings of radiographs and MDCT in patients with thoracic injuries, especially with regard to the thoracic aorta.
Keywords: thoracic injuries; thoracic trauma; arteriography; aortic injuries; thoracic aorta